Prevalence of prolonged transitional neonatal hypoglycemia and associated factors in Ethiopia: A systematic review and meta-analysis - Solomon Demis Kebede; Amare Kassaw; Tigabu Munye Aytenew; Kindu Agmas; Demewoz Kefale (PLoS ONE, 2025)
Introduction Most neonates experience transient hypoglycemia, which typically responds well to treatment and is associated with a favorable prognosis. However, hypoglycemia persisting beyond 48 hours, termed prolonged transitional Neonatal hypoglycemia (PTNHG), can result in abrupt neuronal injury and long-term neurodevelopmental impairments. Identifying its prevalence and associated risk factors is critical to inform clinical practices and improve neonatal outcomes. Methods A weighted inverse-variance random-effects model was employed for the analysis. Heterogeneity among the studies was assessed using a forest plot, I2 statistics, and Egger’s test. Data extraction was conducted from May 20 to May 27, 2023, for studies published since 2020. A random blood sugar (RBS) concentration of <47 mg/dL measured 48–72 hours after birth was used to define PTNHG. Eight studies comprising a total of 3686 neonates were included in the analysis. Results The pooled prevalence of PTNHG was 19.71% (95% CI: 16.85–22.56) with substantial heterogeneity (I2 = 79.20%, P < 0.001). Subgroup analysis revealed that PTNHG prevalence was similar for studies with sample sizes >400 and ≤400, at 18% (95% CI: 15–22) and 21% (95% CI: 17–26), respectively. Similarly, prevalence estimates were comparable when using RBS thresholds of <47 mg/dL (21%; 95% CI: 16–27) and <40 mg/dL (18%; 95% CI: 15–22). Significant factors associated with PTNHG included preterm birth (AOR = 3.31; 95% CI: 2.57–4.04), hypothermia (AOR = 3.41; 95% CI: 2.19–4.62), being an infant of a diabetic mother (IDM) (AOR = 4.71; 95% CI: 2.15–7.26), delayed breastfeeding initiation beyond one hour (AOR = 3.26; 95% CI: 2.03–4.49), and pathological jaundice (AOR = 2.37; 95% CI: 1.91–2.84). Conclusions Nearly one-fifth of hospitalized neonates experienced PTNHG. Fortunately, most of the associated risk factors were modifiable. Prioritizing early breastfeeding initiation, particularly in cesarean section deliveries and IDM cases, and integrating PTNHG management into national NICU guidelines could significantly reduce the burden of neonatal hypoglycemia. Trial registration Prospero ID: CRD42023424953. https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023424953.